THE ROLE OF ENTREPRENEURIAL LEADERSHIP IN ENHANCING ORGANIZATIONAL CONFIDENCE IN MOBILE TELECOMMUNICATIONS COMPANIES/A CASE STUDY IN ZAIN TELECOMMUNICATIONS - Adnan Rashed Awad (Scholars Digest Publishing, 2023)
The research aimed to analyze the relationship between entrepreneurial leadership as an independent variable and organizational trust as a dependent variable in mobile communication companies, as well as testing the extent of the impact of entrepreneurial leadership on organizational trust in that company. The method of intentional sampling was adopted, which amounted to (174) to a group of (113) individuals distributed among them. The questionnaire was conducted using the direct method, and (111) questionnaires were retrieved that were suitable for analysis. The research found that entrepreneurial leadership practices are available to a high degree among the research sample. Also, the level of organizational confidence came to a moderate degree, and it became clear that there is a positive, statistically significant relationship between entrepreneurial leadership and organizational confidence, as the greater the role of entrepreneurial leadership, the higher the levels of organizational confidence. employees, as well as the presence of a positive moral effect of the dimensions of entrepreneurial leadership on organizational confidence. At the end of the research and in light of the results of the statistical analysis of the data, a set of recommendations were developed that contribute to enhancing entrepreneurial leadership practices among employees of mobile telecommunications companies in order to raise the level of organizational confidence